Integrating scholarship and continuing professional development (CPD) in the natural sciences at a South African university - Frick, Beatrice Liezel (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2007.